PENGARUH LIKUIDITAS, LEVERAGE, DAN INTENSITAS MODAL TERHADAP AGRESIVITAS PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Diasya Zulfa Ramdhania; Hayu Wikan Kinasih (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
This study aims to examine the effect of liquidity, leverage, capital intensity on tax aggressiveness, and moderated by company size. This study conducted in manufacturing entities listed on the IDX (Indonesia Stock Exchange) over the period of 2017-2019. This study used 63 manufacturing companies and 181 samples. The method of analysis used in this research is multiple linear regression and moderated regression analysis(MRA) to prove the role of moderating variabel. The results show that Leverage had an effect on tax aggressivenes, whereas liquidity,capital intensity and firm size had no effect on tax aggressivenes. This study also prove that firm size weakens the relationship between leverageand tax aggressiveness, while firm size not proven as a moderating variable on the relationship between liquidity, capital intensity on tax aggressiveness. Keywords: liquidity, leverage, capital intensity, company size and tax aggressiveness